Feature & magazine writing : action, angle and anecdotes - Sumner, David E.; Sumner, David E. (West Sussex, U.K. Wiley-Blackwell, 2013)
"Updated with fresh facts, examples and illustrations, along with two new chapters on digital media and blogs this third edition continues to be the authoritative and essential guide to writing engaging and marketable feature stories. Covers everything from finding original ideas and angles to locating expert sources Expanded edition with new chapters on storytelling for digital media and building a story blog Captivating style exemplifies the authors' expert guidance Authors combines academic authority with professional know-how Comprehensive coverage of all the angles, including marketing written work and finding jobs in the publishing industry Essential reading for anyone wishing to become a strong feature writer "--
Part I: Reading, writing and relevance -- Part II: Taking your articles to the freelance market -- Part III: Adding action and anecdotes -- Part IV: Different formats, different results -- Part V: Exploring digital opportunites -- Part VI: Preparing the final draft.
Includes bibliographical references and index.
Keywords: Feature writing. -- Journalism; Journalism -- Authorship; Magazine writing -- Technique; LANGUAGE ARTS & DISCIPLINES / Communication Studies